Maturation of human intestinal organoids in vitro facilitates colonization by commensal lactobacilli by reinforcing the mucus layer. Issue 8 (30th June 2020) - Son, Ye Seul; Ki, Soo Jin; Thanavel, Rajangam; Kim, Jong‐Jin; Lee, Mi‐Ok; Kim, Janghwan; Jung, Cho‐Rok; Han, Tae‐Su; Cho, Hyun‐Soo; Ryu, Choong‐Min; Kim, Sang‐Heon; Park, Doo‐Sang; et al.
Abstract: Lactobacilli, which are probiotic commensal bacteria that mainly reside in the human small intestine, have attracted attention for their ability to exert health‐promoting effects and beneficially modulate host immunity. However, host epithelial‐commensal bacterial interactions are still largely unexplored because of limited access to human small intestinal tissues. Recently, we described an in vitro maturation technique for generating adult‐like, mature human intestinal organoids (hIOs) from human pluripotent stem cells (hPSCs) that closely resemble the in vivo tissue structure and cellular diversity. Here, we established an in vitro human model to study the response to colonization by commensal bacteria using luminal microinjection into mature hIOs, allowing for the direct examination of epithelial‐bacterial interactions. Lactobacillus reuteri and Lactobacillus plantarum were more likely to survive and colonize when microinjected into the lumen of mature hIOs than when injected into immature hIOs, as determined by scanning electron microscopy, colony formation assay, immunofluorescence, and real‐time imaging with L plantarum expressing red fluorescent protein. The improved mature hIO‐based host epithelium system resulted from enhanced intestinal epithelial integrity via upregulation of mucus secretion and tight junction proteins. Our study indicates that mature hIOs are a physiologically relevant in vitro model system for studying commensal microorganisms.